1998
DOI: 10.1097/00003446-199804000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Field Sensitivity of Targeted Neonatal Hearing Screening using the Nottingham ABR Screener

Abstract: Neonatal hearing screening in an at-risk population using a highly automated ABR test is a viable and effective tool for identification of hearing impairment. Although the field sensitivity of the test is high, it is unable to identify all babies with a criterion level of hearing loss. There are a number of possible explanations as to the origin of false negative results: configuration of the pure-tone audiogram, a progressive hearing loss, acquired sensorineural or conductive loss, retrocochlear deafness, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…In this prospective study no false negatives were found at follow-up, which made the AABR neonatal hearing screening of great value in the total evaluation of the at-risk newborn, in which anticipation of probable disorders of neurological development is an important part of the follow-up. In a retrospective study of the Nottingham AABR screener used in a NICU population Mason et al (24) reported a sensitivity of 90% and a specificity of 93%, which compares favourably with the results of OAE screening in an equivalent group, which had a sensitivity of 80% and a specificity of 92% (24,25).…”
Section: Automated Auditory Brainstem Response Screening In the High-mentioning
confidence: 91%
“…In this prospective study no false negatives were found at follow-up, which made the AABR neonatal hearing screening of great value in the total evaluation of the at-risk newborn, in which anticipation of probable disorders of neurological development is an important part of the follow-up. In a retrospective study of the Nottingham AABR screener used in a NICU population Mason et al (24) reported a sensitivity of 90% and a specificity of 93%, which compares favourably with the results of OAE screening in an equivalent group, which had a sensitivity of 80% and a specificity of 92% (24,25).…”
Section: Automated Auditory Brainstem Response Screening In the High-mentioning
confidence: 91%
“…We therefore sought 15 papers 3,7,8,26,[43][44][45][46][47][48][49][50][51][52][53] for full review. All but one 45 (published in 1981) were published between 1996 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Four of the studies reported comparisons of two different screening tests without reference standards, [44][45][46][47] two of the studies (identified from the search on negligence) reported no cases owing to missed diagnosis of hearing impairment, 48,49 and three included general discussion of the value of hearing screens beyond the neonatal period. 8,50,51 These nine studies were not reviewed further.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In preterm babies Brienesse could detect a click-evoked OAE in 69% of the attempts, of which 40% had a reproducibility above 40% and 44% reached a signal-to-noise ratio b3 dB (22). In a retrospective study of the Nottingham AABR screener used in a NICU population Mason et al (24) reported a sensitivity of 90% and a specificity of 93%, which compares favourably with the results of OAE screening in an equivalent group, which had a sensitivity of 80% and a specificity of 92% (24,25). It is feasible for use on the ward and in the incubator, even during nasal CPAP oxygen therapy or artificial ventilation, without disturbance from either ambient noise or technical equipment.…”
Section: Automated Auditory Brainstem Response As a Universal Screenimentioning
confidence: 96%